SURFACE CHEMISTRY OF KAOLINITE AND NA-MONTMORILLONITE IN AQUEOUS ELECTROLYTE SOLUTIONS AT 25 AND 60 °C: EXPERIMENTAL AND MODELING STUDY - Tertre E.; Castet S.; Berger G.; Loubet M.; Giffaut E. (My University, 2006)
The aqueous interfacial chemistry of kaolinite and Na-montmorillonite samples was investigated by potentiometric measurements using acid/base continuous titrations and batch experiments at 25 and 60 °C. Using the batch experimental method, a continuous drift of pH was observed reflecting the mineral dissolution. Consequently, the continuous titration method appears to be the best way of studying solid surface reactions. For each clay mineral, the net proton surface excess/consumption was calculated as a function of pH and ionic strength (0.025, 0.1 and 0.5 M). At 25 °C, and according to the literature data, the pH corresponding to zero net proton consumption for montmorillonite appears to depend on ionic strength, whereas the value for kaolinite is constant and close to 5. Similar results are obtained at 60 °C, which suggests that the point of zero net proton consumption for clay minerals does not depend on temperature, at least up to 60 °C. On the other hand, the temperature rise induces a slight increase of the net proton surface excess. Finally, the diffuse double layer formalism (DDLM) is used to model the experimental data. The model involves two processes: the protonation/deprotonation of two types of edge sites (aluminol and silanol) and H +/Na + exchange reactions on basal surfaces, while a tiny proportion of the negative structural charge remains uncompensated. This last process maintains a negative surface potential whatever the pH of the solution, which is in agreement with electrokinetic data. © 2006 Elsevier Inc. All rights reserved.